Translation and Adaptation of the Adult Developmental Coordination Disorders/Dyspraxia Checklist (ADC) into European Portuguese Language - Paula Rodrigues; Olga Vasconcelos; Denise Soares; Sónia Gonçalves-Lopes; Cláudia Sousa; Rita Barros (Psychologica)
This paper reports the psychometric characteristics of the Portuguese version of the Adult Developmental Coordination Disorders/Dyspraxia Checklist (ADC). An independent translation of the questionnaire from the original version into European Portuguese was conducted. The sample consisted of 346 Portuguese adults, aged 18 to 65 years. Analyses were performed using R software (version 4.1.0). Exploratory factor analysis was performed to analyze the factor structure of the ADC scale, and a shorter 32-item version was found, with three new factors related to adaptation and daily life activities, gross motor coordination regarding ludic and physical activities that involve major muscular groups, and fine motor coordination activities. The Portuguese version demonstrated adequate reliability, as measured by internal consistency, item-total correlations, and test-retest reliability. All three factors and total scores were positively correlated with age. Gender differences were only found for the ludic and physical activities factor, with women presenting a higher score (more difficulties). This is a smaller-scale version that has good psychometric properties, making it a suitable alternative to the original scale when applied to Portuguese adults.